A Study on Undergraduate English Program Modes in China - Siyu Chen; Yining Zhang; Runfeng Li (MDPI AG, 2023)
While English major education is of significant importance in China, there is a lack of comprehensive research that provides a broader perspective, encompassing a thorough exploration and comparison of the diverse program modes employed across different undergraduate English programs in China. The focus of this study is to (1) discern the overarching characteristics of undergraduate English programs in China; (2) identify undergraduate English program modes in China; and (3) delve into the relationship between the identified modes and university discipline evaluation rankings. The dataset includes undergraduate English program handbooks from 50 universities in China and information on 2942 courses extracted from these handbooks. The findings suggest that English programs in universities and colleges in China exhibit a predominantly application-oriented approach. In addition, three modes were identified: Literature and Linguistics, Balanced, and High English Skills. The High English Skill mode was found to be linked with a lower ranking compared to the High Literature and Linguistics mode. The study concludes by offering implications for the design of a future English program based on the insights gained from the analysis.